New insights learned from the pulmonary to systemic blood flow ratio to predict the outcome in patients with hypoplastic left heart syndrome in the pre-Glenn stage: a single-center study - Mini, Nathalie; Zartner, Peter A.; Schneider, Martin B. E. (Frontiers in Cardiovascular Medicine, 2023)
Background: To the best of our knowledge, no study was made until now to determine whether the ratio between pulmonary and systemic flow (QP: QS) in the pre-Glenn-stage (PGS) can predict the outcome in patients with hypoplastic left heart syndrome (HLHS) who underwent Norwood palliation. Methods: Between January 2016 and August 2022, 80 cardiac catheterizations in 69 patients with HLHS in stage NW palliation with modified Blalock-Taussig shunt (MBTS) were retrospective recruited. The Qp:Qs ratio was measured under stable conditions using the Fick formula. None of the patients was intubated. Patients were divided into two groups: group 1 includes patients who underwent planned cardiac catheterization (n=56), and group 2 includes patients who underwent unplanned examination (n=13), in which the indication for cardiac catheterization was desaturation in 11 patients and pulmonary overcirculation in 2. Primary outcome was defined as accomplishing the planned operations (Glenn and Fontan) with freedom from death, reoperation, referring to a palliative therapy or heart transplantation. The secondary outcome was defined as freedom from reintervention in MBTS or in pulmonary arteries. Results: The median follow up was 48 months (range 6-72 months). The median QP: QS in group 1 was 1.77 (range 1.5-2.2). In group 2 the 11 patients with desaturation the median value of QP: QS was 1.24 (0.9-1.4). The two patients with suspected pulmonary overcalculation showed a QP: QS of 2.3 and 2.5 respectively, and a reduction of the shunt size was required. The primary outcome was achieved in 96.4% of group 1 compared to only 30.7 % in group 2. The need for reintervention was 1.8% in Group1 compared to 61.3% in group 2. There is a significant relationship between Qp:Qs and the impaired outcome (death, palliative therapy or to heart transplantation) with p. value 0.001 and a relative risk factor (RR) 3.1 Confidence interval (CI) (95%) 1.4-7.1 .Conclusion: QP: QS in PGS can predict the outcome in patients with HLHS in stage Norwood with MBTS. The Qp:QS between 1.5-2.2 with a median of 1.77 seem to be optimal in the patients in PGS. Qp:QS < 1.5 associates pulmonary stenosis, shunt stenosis and pulmonary hypertension.